Reading the Colours of Victorian Interiors: The Poetic Home Revisited - Charlotte Ribeyrol (Cahiers Victoriens et Edouardiens)
The invention of mauveine, the first coal-tar based aniline dye in London in 1856 marked a chromatic turning-point in the history of industrial Europe. Up until the 1870s Britain was in the vanguard of this ‘colour revolution’. Mauve was soon followed by a whole gamut of new, low-priced dyes which radically transformed the experience of colour for all sections of society. As a consequence, the ‘evolution’ of the colour-sense received unprecedented attention, not only from the scientists who made colour production and colour perception their new object of study, but also from artists and writers like John Ruskin or William Morris who placed colour at the centre of the creative process. Surprisingly, this ‘colour revolution’ has only rarely been approached from the perspective of interior decoration despite the fact that from the 1860s an increasing number of periodicals and popular handbooks offered guidance on how to make one’s home ‘poetic’ thanks to the right colour arrangements. In this article I analyse a selection of these ‘colour grammars’ which aimed to channel and control the chromatic ‘chaos’ of modernity, before discussing a unique instance of a well-preserved and poetically colourful interior: the architect William Burges’s Tower House in London.